Prevention of mother-to-child transmission in South Africa: an ever-changing landscape - Burton, Rosie (Obstet Med, 2015)
Almost 30% of pregnant women attending public health clinics in South Africa are HIV positive; which represents approximately 280,000 women each year. South Africa has the largest antiretroviral therapy programme in the world, with over 2.7 million people on treatment in 2013. Since its belated and controversial beginning, the Prevention of Mother-to-Child Transmission programme has achieved a substantial reduction in vertical transmission. South Africa is justifiably proud of this success. However, the history of Prevention of Mother-to-Child Transmission (PMTCT) and antiretroviral therapy programmes in South Africa has been fraught with delays and political intervention. South Africa could have started both PMTCT and antiretroviral therapy programmes in 2000. Instead, the AIDS denialist views of the government allowed the HIV epidemic to spiral out of control. Roll-out of a national PMTCT programme began in 2002, but only after the government was forced to do so by a Constitutional Court ruling. Now, a decade later, HIV treatment and prevention programmes have been completely transformed. This article will discuss the evolution of the HIV epidemic in South Africa, and give a historical overview of the struggle to establish a national PMTCT, and the impact of delaying PMTCT and treatment programmes on infant and maternal health.